2013
DOI: 10.1039/c3tb21296c
|View full text |Cite
|
Sign up to set email alerts
|

The role of poly(aspartic acid) in the precipitation of calcium phosphate in confinement

Abstract: Many questions remain regarding the formation of ultrathin hydroxapatite (HAP) crystals within the confines of collagen fibrils of bones. These structures form through the interplay of the collagen matrix and non-collagenous proteins, and in vitro mineralization studies employing poly(aspartic acid) (PAsp) as a mimic of the non-collagenous proteins have generated mineralized fibrils with structures comparable to their biogenic counterparts. In this article, we employ the nanoscale cylindrical pores perforating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 77 publications
(162 reference statements)
4
54
0
Order By: Relevance
“…We have previously shown that TE membranes provide a versatile means of studying the effects of confinement on the polymorph, orientation, and single-crystal/polycrystalline structure of inorganic crystals (21)(22)(23)(24)(25)(26). Briefly reviewing these studies, our early work employed pores as small as 200 nm and used low temperatures and 100 mM CaCl 2 and Na 2 CO 3 solutions to generate single crystals of calcite via an amorphous calcium carbonate (ACC) precursor phase (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that TE membranes provide a versatile means of studying the effects of confinement on the polymorph, orientation, and single-crystal/polycrystalline structure of inorganic crystals (21)(22)(23)(24)(25)(26). Briefly reviewing these studies, our early work employed pores as small as 200 nm and used low temperatures and 100 mM CaCl 2 and Na 2 CO 3 solutions to generate single crystals of calcite via an amorphous calcium carbonate (ACC) precursor phase (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Confinement plays a key role in the formation of bone, which begins with the growth of ultrathin platelets of nonstoichiometric carbonated hydroxyapatite (HAP) within gaps in the collagen fibrils. 20 These 2-6 nm thick platelets are the smallest known biogenic crystal 21,22 and are organized so membranes to show that confinement alone can direct the orientation of HAP, 42,43 and demonstrate that both octacalcium phosphate (OCP) and amorphous calcium phosphate (ACP) can be effectively stabilized in confinement. Consideration of the mechanism by which confinement increases the lifetime of these phases suggests that is distinct from that found with CaCO 3 and CaSO 4 , and emphasizes the need to study multiple systems to fully understand the effects of confinement on crystallization processes, and therefore to employ confinement as a route to controlling crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…This is different from PAsp-induced mineralization, in which PAsp infiltrates the collagen and preferentially binds in the gap zones, promoting intrafibrillar mineralization. Although there is evidence that PAsp may act as an inhibitor when not bound to collagen [60]. Prior studies examining the mineralization of dense collagen scaffolds with fetuin have demonstrated similar results: mineralization occurs preferentially within the matrix, often concentrated near the surface, likely due to diffusion limitations [20,53,61].…”
Section: Discussionmentioning
confidence: 84%